PENINGKATAN KOMPETENSI GURU DALAM MENERAPKAN PEMBELAJARAN DARING MASA PANDEMI COVID-19 DI SDN IMPRES KINANDAL KECAMATAN LIANG KABUPATEN BANGGAI KEPULAUAN: SDN IMPRES KINANDAL KECAMATAN LIANG KABUPATEN BANGGAI KEPULAUAN - YOSES KALANDING (Dewan Pendidikan Bondowoso, 2022)
This study aims to improve the ability of teachers to apply online learning during the Covid 19 pandemic at SDN Impres Kinandal. The type of research used by the author in this research is school action research. According to Arikunto (Suyadi, 2012), PTS is a combination of meanings from the words